The nexus of auditor, firm characteristics and governance in influencing key audit matters: a study of financial firms in Indonesia - Soepriyanto, Gatot; Utomo, Hermin (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2025)
This study explored the determinants of Key Audit Matters (KAMs) within the financial sector of Indonesia, an emerging market characterized by distinctive socio-economic and cultural dynamics. It examined the impact of auditor characteristics, firm attributes, and corporate governance mechanisms on KAM disclosures, particularly in the wake of the recent incorporation of International Standard on Auditing 701 (ISA 701) into Indonesian audit practices. The study employed a comprehensive approach, utilizing statistical techniques such as correlation analysis, Ordinary Least Squares (OLS) regression, and descriptive analysis validated by Mann-Whitney test. Drawing upon an exclusive dataset of financial firm observations in 2022—the first period when KAM disclosures were required—the research investigated the associations between KAM disclosures and various risk factors based on firm risk, auditor, and governance characteristics. The findings showed that while Big 4 affiliation, audit fees, and female auditors significantly predicted KAM disclosures, firm risks such as solvency, profitability, liquidity, and cost efficiency also emerged as critical. Surprisingly, governance characteristics showed no significant bearing on KAM disclosures, which underscored the dominance of auditor and firm risk attributes in shaping KAM disclosures within the regulated, scrutinized Indonesian financial sector.